Somatic Embryogenesis Direct And Indirect On Porang Plants (Amarpopallus oncophilus) - Mohammad Nur Khozin; Didik Pudji Restanto; Dwi Erwin Kusbianto (Faculty of Agriculture University of Singaperbangsa Karawang, 2022)
ABSTRACT Propagation of conjact using somatic embryogenesis techniques either directly or indirectly gives hope procuring large quantities of seeds. This study aims to evaluate the method of direct and indirect somatic induction of embryogenesis from conjact. In vitro porang leaves were used as explants. The media used is Murashige and Skoog (MS) media with a combination of NAA and BAP. The results showed that in vitro porang leaf explants cultured in media containing BA 2.22 M could induce embryosomatics directly, whereas media containing single 20 M NAA and a combination of NAA 20 M + BA 2.22 M induced direct and or indirect embryosomatics. . The best medium for induction was shown by 20 M NAA media which had 100% SE induction percentage and fast time.relatively. Keywords: Conjact, somatic embryogenesis, hormones, direct, indirect.